Practical data analysis with JMP - Carver, Robert H. (SAS Institute, 2014)
This book uses the powerful interactive and visual approach of JMP to introduce readers to the logic and methods of statistical thinking and data analysis. It enables you to discriminate among and to use fundamental techniques of analysis, enabling you to engage in statistical thinking by analyzing real-world problems. "Application Scenarios" at the end of each chapter challenge you to put your knowledge and skills to use with data sets that go beyond mere repetition of chapter examples, and three new review chapters help readers integrate ideas and techniques. In addition, the scope and sequence of the chapters have been updated with more coverage of data management and analysis of data. The book can stand on its own as a learning resource for professionals or be used to supplement a standard college-level introduction-to-statistics textbook. Reflective of the broad applicability of statistical reasoning, the problems included inthe book come from a wide variety of disciplines, including engineering, life sciences, business, economics, among others, and include a number of international and historical examples. --